1998
DOI: 10.1016/s0022-5223(98)70220-x
|View full text |Cite
|
Sign up to set email alerts
|

Improved efficiency of energy transfer to external work in chronic cardiomyoplasty based on the pressure-volume relationship

Abstract: Dynamic cardiac compression in the form of cardiomyoplasty enhanced left ventricular pump performance without interrupting left ventricular filling. The ratio of energy transfer from the native pressure-volume area to the overall external work suggests a myocardial oxygen-sparing effect of cardiomyoplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 28 publications
(44 reference statements)
1
1
0
Order By: Relevance
“…Such external compressive engagement of the Frank-Starling mechanism has only been previously observed with dynamic cardiomyoplasty. [26][27][28] Our results have demonstrated that this dynamic enhancement capability also extends to the HeartPatch DCC device, with Ees increasing from 0.8 to 11 mm Hg/mL with biventricular DCC. We propose that this relates to the device's ''nonsurround'' design, aimed at removing the constrictive effects of its ''heart-surround'' counterparts.…”
Section: Load-independent Response Of Rv To DCCsupporting
confidence: 55%
See 1 more Smart Citation
“…Such external compressive engagement of the Frank-Starling mechanism has only been previously observed with dynamic cardiomyoplasty. [26][27][28] Our results have demonstrated that this dynamic enhancement capability also extends to the HeartPatch DCC device, with Ees increasing from 0.8 to 11 mm Hg/mL with biventricular DCC. We propose that this relates to the device's ''nonsurround'' design, aimed at removing the constrictive effects of its ''heart-surround'' counterparts.…”
Section: Load-independent Response Of Rv To DCCsupporting
confidence: 55%
“…Additional support for this premise was reflected in the greater RV SW values seen in the IV septal-ablated sheep during RV patch actuation, which also explains, by way of reciprocation, the lower RV SW values observed in the PTSMA sheep during univentricular LV DCC (Figure 4). Our previous studies have shown that cardiomyoplasty can also enhance external SW. 28 We have previously shown, under closed chest conditions, that PTSMA alone leads to prolonged Tau. 17 However, we did not observe this in the present study, in which Tau was paradoxically reduced by IV septal ablation.…”
Section: Load-dependent and Rv Diastolic Response To DCCmentioning
confidence: 93%